2022
DOI: 10.1002/aesr.202200152
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanomaterials‐Enabled High‐Performance Supercapacitors: A Review

Abstract: Supercapacitors (SCs), an important kind of electrochemical energy storage device, are featured with high power density, rapid charging and discharging, and ultralong cycling lifespan and have been widely applied in multiscenario energy storage and output systems, such as portable consumer electronics, electric vehicles, and reservoir setups for green and sustainable energy resources. Among their components, electrode materials are of primary importance in dictating their performances. Owing to good electric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 200 publications
0
2
0
Order By: Relevance
“…These attributes make CNPs ideal candidates for electrode materials in supercapacitor devices, enabling efficient charge storage and highpower delivery [5]. Several studies have shown how CNPs can improve supercapacitors' performance, which results in better energy storage capacity, improved charge-discharge kinetics, and longer cycle life [6]. In addition to carbon-based materials, metal oxide nanomaterials have also emerged as promising candidates for supercapacitor applications [7].…”
Section: Introductionmentioning
confidence: 99%
“…These attributes make CNPs ideal candidates for electrode materials in supercapacitor devices, enabling efficient charge storage and highpower delivery [5]. Several studies have shown how CNPs can improve supercapacitors' performance, which results in better energy storage capacity, improved charge-discharge kinetics, and longer cycle life [6]. In addition to carbon-based materials, metal oxide nanomaterials have also emerged as promising candidates for supercapacitor applications [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, this superior performance would disappear when talking about a bulk electrode composed of graphene units. For instance, the capacitance of reduced graphene oxide (r-GO) prepared by traditional Hummer’s method is usually in the range of 100–200 F g −1 , much lower than the theoretical value of 550 F g −1 ; this majorly results from the reduced specific surface area and the shortage of ion/electron transport rate [ 5 , 6 , 7 , 8 ]. Therefore, the three-dimensional r-GO hydrogel electrodes with thin nano-graphite walls that are composed of several layers of graphene are preferred.…”
Section: Introductionmentioning
confidence: 99%